AB0176 Association between Polymorphisms in Beta-Adducin and Sodium/Calcium Exchanger 1 and SLE with and without Nephritis. (10th June 2014) - Ramirez, G.A.; Bozzolo, E.P.; Casamassima, N.; Lanzani, C.; Manunta, P.; Canti, V.; Rovere-Querini, P.; Sabbadini, M.G.; Manfredi, A.A.
Abstract : Background: Genes involved in cytoskeletal assembly and water/electrolyte balance have been previously linked to hypertension, but recent evidences suggest a role also in the development of inflammation and autoimmunity [1-2]. Systemic Lupus Erythematosus is a prototypic multi-organ autoimmune disease, characterized by polymorphic clinical features and a complex polygenic background. Renal disease in SLE occurs in 40-70% of lupus patients and is responsible of an high burden of morbidity and mortality. Despite substantial efforts, less is known about the role of specific genetic factors in conferring susceptibility to SLE and its complications, including lupus nephritis (LN) [3]. Objectives: With these premises we sought if an association between known hypertension-related polymorphisms and development of SLE and LN existed. Methods: 106 patients (96 females, 10 males) diagnosed with SLE (n=51) or LN (n=55), 23 patients with Sjoegren's Syndrome and 62 healthy controls were enrolled. Patients and controls were genotyped for polymorphisms in α-, β- and γ-adducin (ADD1, 2, 3 respectively), angiotensin converting enzyme, transient receptor potential cation channel-subfamily C, solute carrier family 8 (sodium-calcium exchanger) member 1 (SLC8A1), solute carrier family 24 (sodium/potassium/calcium exchanger) member 3, PKD2 calcium channel and PRKG1 kinase genes. Results: Beta-adducin (ADD2) rs4984 CT heterozygosis was significantly more frequent in SLE patients than in LN patients (χ 2 =6.154; p=0.013). No patient had the ADD2 rs4984 TT genotype in accordance with a low prevalence of the ADD2 C1797T homozygosity in the population. Seven patients with SLE (n=3) or LN (n=4), but none of the control groups carried the AA variant of sodium/calcium exchanger 1 (SLC8A1) rs11893826 SNP (χ 2 =11.771; p=0.019). Conclusions: Genes involved in the control of electrolyte/water balance and cytoskeletal plasticity could affect the pathogenic background of SLE/LN. Larger studies are required to confirm these data and attempt correlations between genetic data and specific clinical features. References: Tintinger GR, et al., Drug Des Devel Ther, 2009 Kleinewietfeld M, et al., Nature, 2013 Ramos PS, et al., Semin Nephrol, 2010 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3378